2020
DOI: 10.1136/gutjnl-2020-322509
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin synthase 1 mediates hepatocyte pyroptosis to trigger non-alcoholic steatohepatitis

Abstract: ObjectiveLipotoxic hepatocyte injury is a primary event in non-alcoholic steatohepatitis (NASH), but the mechanisms of lipotoxicity are not fully defined. Sphingolipids and free cholesterol (FC) mediate hepatocyte injury, but their link in NASH has not been explored. We examined the role of free cholesterol and sphingomyelin synthases (SMSs) that generate sphingomyelin (SM) and diacylglycerol (DAG) in hepatocyte pyroptosis, a specific form of programmed cell death associated with inflammasome activation, and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 49 publications
6
76
1
Order By: Relevance
“…Mechanistically, it is unclear how GSDMD is activated by hyperglycaemia in macrophages. A recent study revealed the leading role of NLRC4‐dependent pyroptosis in steatohepatitis (Koh et al, 2020). Following our previous findings that NLRC4 phosphorylation plays an important role in hyperglycaemia (P. Zhang, Wang, et al, 2019), we investigated the role of NLRC4 in pyroptotic cell death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, it is unclear how GSDMD is activated by hyperglycaemia in macrophages. A recent study revealed the leading role of NLRC4‐dependent pyroptosis in steatohepatitis (Koh et al, 2020). Following our previous findings that NLRC4 phosphorylation plays an important role in hyperglycaemia (P. Zhang, Wang, et al, 2019), we investigated the role of NLRC4 in pyroptotic cell death.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study revealed that NLRC4 is responsible for IL‐1β production and macrophage infiltration in diabetic nephropathy (F. Yuan et al, 2016). In addition, NLRC4‐dependent pyroptosis, but not NLRP3, plays a significant role in steatohepatitis (Koh et al, 2020). Therefore, in this study, we assessed NLRC4 in hyperglycaemia‐induced pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 210 Sphingomyelin synthases (SMSs) could generate sphingomyelin (SM) and diacylglycerol (DAG), while free cholesterol and SMSs in hepatocytes are found to mediate hepatocyte pyroptotic injury through DAG‐PKCδ‐NLRC4 axis. 211 It has been reported that geranylgeranoic acid (GGA) (C20:4) could induce pyroptotic cell death in human hepatoma‐derived HuH‐7 via toll‐like receptor 4 (TLR4) signaling pathway. In fact, GGA is a branched‐chain polyunsaturated fatty acid, an endogenous metabolite derived from the mevalonate pathway in mammals.…”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
“…A possible explanation is that PA‐related pyroptosis may contribute to endoplasmic reticulum (ER) stress in HepG2 cells, and OA is capable of improving hepatocellular lipotoxicity both in vitro and in vivo 210 . Sphingomyelin synthases (SMSs) could generate sphingomyelin (SM) and diacylglycerol (DAG), while free cholesterol and SMSs in hepatocytes are found to mediate hepatocyte pyroptotic injury through DAG‐PKCδ‐NLRC4 axis 211 . It has been reported that geranylgeranoic acid (GGA) (C20:4) could induce pyroptotic cell death in human hepatoma‐derived HuH‐7 via toll‐like receptor 4 (TLR4) signaling pathway.…”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
“…In response to potassium efflux, the NIMA (never in mitosis, gene A) related kinase 7 acts as an essential partner that interacts with NLRP3 and licenses its activation (20,21). In addition, cross-talk between NLRP3 and NLRC4 was revealed by studies in Escherichia coli-and Salmonella typhimurium-induced inflammation (22)(23)(24) and in sterile inflammation induced by lysophosphatidylcholine (LPC), hyperosmotic stress, or diacylglycerol (DAG) (25)(26)(27)(28). During S. typhimurium infection, NLRP3 and NLRC4 can be recruited to same macromolecular complex through ASC (29,30).…”
Section: Introductionmentioning
confidence: 99%